A dual-flow RootChip enables quantification of bi-directional calcium signaling in primary roots - Allan, Claudia; Tayagui, Ayelen; Hornung, Rainer; Nock, Volker; Meisrimler, Claudia-Nicole (Frontiers in Plant Science, 2023)
One sentence summary: Bi-directional-dual-flow-RootChip to track calcium signatures in Arabidopsis primary roots responding to osmotic stress. Plant growth and survival is fundamentally linked with the ability to detect and respond to abiotic and biotic factors. Cytosolic free calcium (Ca2+) is a key messenger in signal transduction pathways associated with a variety of stresses, including mechanical, osmotic stress and the plants’ innate immune system. These stresses trigger an increase in cytosolic Ca2+ and thus initiate a signal transduction cascade, contributing to plant stress adaptation. Here we combine fluorescent G-CaMP3 Arabidopsis thaliana sensor lines to visualise Ca2+ signals in the primary root of 9-day old plants with an optimised dual-flow RootChip (dfRC). The enhanced polydimethylsiloxane (PDMS) bi-directional-dual-flow-RootChip (bi-dfRC) reported here adds two adjacent inlet channels at the base of the observation chamber, allowing independent or asymmetric chemical stimulation at either the root differentiation zone or tip. Observations confirm distinct early spatio-temporal patterns of salinity (sodium chloride, NaCl) and drought (polyethylene glycol, PEG)-induced Ca2+ signals throughout different cell types dependent on the first contact site. Furthermore, we show that the primary signal always dissociates away from initially stimulated cells. The observed early signaling events induced by NaCl and PEG are surprisingly complex and differ from long-term changes in cytosolic Ca2+ reported in roots. Bi-dfRC microfluidic devices will provide a novel approach to challenge plant roots with different conditions simultaneously, while observing bi-directionality of signals. Future applications include combining the bi-dfRC with H2O2 and redox sensor lines to test root systemic signaling responses to biotic and abiotic factors.